Estrategia didáctica de signos y señales en el proceso de enseñanza aprendizaje - Cajas Quinatoa, Silvia Abigaíl (2022)
The didactic strategies through signs and signals, promotes that people learn the oral language and consequently favors learning. The objective of the research is to structure didactic strategies of signs and signals in the classroom to strengthen the teaching-learning process in children of first and second year of Basic Education of the Specialized Educational Unit of Cotopaxi in the academic period 2022. The methodology is based on the quantitative approach, it allows the collection and analysis of data to answer research questions, the type of research is descriptive, because it tries to collect quantifiable information to be used in the statistical analysis of the population sample, as for the instrument, surveys were applied to teachers. In relation to the proposal, the following learning strategies were established for students with hearing difficulties: Illustrations, Concept Map, Dialogue, and Card Making. The results reflect an active participation of children with hearing difficulties, better communication with teachers and classmates; therefore, the discussion of results is oriented to promote in educational institutions the prioritization of didactic strategies through the mastery of sign language to make effective the teaching-learning process in populations of children with specific needs.